Incompleteness and redundancy: organisational components of a design-enabled infrastructure to support coordinated action of multiple stakeholders. Issue 4 (2nd October 2019) - Simeone, Luca
ABSTRACT: This paper analyses an R&D project funded by the European Commission and aimed at studying, testing and implementing technological and gamification-based solutions for hearing impairment. In the course of the last three years,  a variety of stakeholders with their different wants and needs, languages and agendas have interacted within the project. Particularly, this paper focuses on (1) how the project has built a design-enabled infrastructure to support the interplay of these stakeholders and (2) on how some specific organisational dimensions of this infrastructure - namely incompleteness, and redundancy - favoured coordinated action. Even though the concept of infrastructure has been thoroughly examined in design research, the organisational dimensions that allow to at least partially control divergences and convergences among the various stakeholders remain understudied. To address this gap, this paper intends to offer a contribution at the intersection of design research and organisational studies.